(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Takhaui Akhtanov in the novel “Sorrow of love” which is published in 60th of the XX century describes human inner world different phenomenon, happiness and sadness together. The author creates composition to the personage inside struggle is the main pecularities of the novel. The writer describes the personages different reflection of the soul without any repitation by a size. Т.Akhtanov in the novel "Sorrow of love" gives opening character that selfishness makes a man unmoral. The writer describes selfishness is not as a natural disability, but it is a large social illness. Т. Akhtanov not only disrobes unpleasant qualities in human being, he wanted to open from where, from what it is appeared. Т.Akhtanov’s "Sorrow of love" novel is the artistic work which shows that the author is a great master of making psychological analysis. The achievement of the novel "Sorrow of love" is describing the compositional wholeness and deeply opening the character’s psychology, the personage inner world, the character’s happiness and sadness, also showing at that moment trembly beating of heart and sense of melody with real pictorial sensibility, with psychologist particular ability. The novel opens to the 60th year’s novel fertile channel to the psychology and lyrism. The author also tried to show the writer′s artistic description of psychology and man′s untalented, selfishness problem which is the outside of honesty.